Solubility of carbon, manganese and silicon in γ-iron of Fe-Mn-Si-C alloys - Filonenko, N. Y.; Babachenko, O. I.; Kononenko, G. A.; Domina, K. G. (Physics and Chemistry of Solid State, 2020)
The study was performed on alloys with a carbon content of 0,37-0,57 % (wt.), silicon 0,23-0,29 % (wt.), manganese 0,7-0,86 % (wt.), the rest– iron. To determine the phase composition of alloys used microstructural, microanalysis and X-ray analysis. In addition, the physical characteristics of the alloys studied in this paper were determined, such as alloy chemical dependence of extension and contraction ratio, impact toughness and hardness. The results obtained in this paper showed that the iron-based alloy with the content of carbon of 0.57 % (wt.), silicon of 0.28 % (wt.) and manganese of 0.86 % (wt.)) had the superior microstructure and physical properties. It was determined that after a number of crystallization and phase transformation the alloy phase structure includes two phases: a-iron and cement magnesium doping Fe2.7Mn0,3C.. For the first time using the method quasichemistry received an expression of the free energy of a γ-iron alloyed with silicon and magnesium, and determined the solubility limit of carbon, manganese and silicon. The maximum content in γ-iron can reach: carbon 6,8 % (at.), manganese – 67,5 % (at.), silicon – 2,3 % (at.).